A study of the effectiveness of powerpoint application in teaching visual art at SMK TTDI Jaya / Nurul Jannah Che Razali - Che Razali, Nurul Jannah (2014)
This study focuses on the use of PowerPoint Presentation: Catan Tingkatan 3 as an effective teaching aid. This PowerPoint presentation is built to help the teachers of Visual Art Education in the teaching and learning process. Powerpoint Presentation: Catan Tingkatan 3 is a unique teaching aid because it is multimedia-based teaching materials that are easy to use and equipped with impressive multimedia features. The study also examined the effectiveness of PowerPoint Presentation: Catan Tingkatan 3, which is built based on the ASSURE model to ensure its effectiveness as a teaching medium. One participant for the study is Visual Art Education teacher from Shah Alam. Research instruments used in this study were interview and observation.